2016
DOI: 10.1177/1757743816653151
|View full text |Cite
|
Sign up to set email alerts
|

Employability: The missing voice: How student and graduate views could be used to develop future higher education policy and inform curricula

Abstract: The student voice is currently absent from the employability agenda for higher education in the UK. A government-led neo-liberal model of employability, claiming what employers want when employing graduates, has been uncritically adopted by many universities in the UK to inform higher education strategy and policy. Many undergraduates and graduates perceive this employability model as incongruent and disingenuous to their experiences in gaining and sustaining work. The dominant employability discourse masks in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…In the works of foreign scientists (Hanes, Kemper & Mulhern, 1986;Elliston, 1988) the problems of the design of educational programs providing a high level of practical training for students under the programs of pedagogical, engineering, and managerial education are analyzed. Notes the importance of taking into account the position of students, their professional perspectives in the design of higher education educational programs (Hendel, 1985;Higdon, 2016).…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…In the works of foreign scientists (Hanes, Kemper & Mulhern, 1986;Elliston, 1988) the problems of the design of educational programs providing a high level of practical training for students under the programs of pedagogical, engineering, and managerial education are analyzed. Notes the importance of taking into account the position of students, their professional perspectives in the design of higher education educational programs (Hendel, 1985;Higdon, 2016).…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…As student identities are reframed in marketized terms, that is, as 'customers' and 'consumers' of HE, the implication is that students have higher expectations of what they should receive from universities (Guolla 1999;Rolfe 2002;Mark 2013). 'Value for money' becomes akin to a 'gold standard' for Higher Education Institutions wishing to maintain their competitive advantage in an ever-expanding market (Wilkins et al 2012;Dean and Gibbs 2015;Higdon 2016). If universities do not meet or exceed student expectations-a prerequisite for positive evaluations of service quality (Alves and Raposo 2009)-then complaints are likely to be made, whether this is done informally via word of mouth or more formally through an array of procedures and regulatory bodies (Khoo et al 2017).…”
Section: The Rise In Numbers Of Student Complaintsmentioning
confidence: 99%
“…This setting is traced in the studies that justify the need for a more active role of key participants in the decision-making process [8]. It is concluded that feedback is important not only for trivial issues, but also for the development of the educational system as a whole, including the content and the trend of innovative educational projects [9]. This approach is designed to improve the quality of educational services, and, accordingly, the performance of schoolchildren [10].…”
Section: Introductionmentioning
confidence: 99%